THE IMPACTS OF THE CHANGING NATURE OF WARFARE ON INTELLIGENCE COLLECTION AND PROCESSING - David Holtz (The Journal of Intelligence, Conflict and Warfare)
On November 20, 2024, Lieutenant-Colonel. David Holtz presented The Impacts of the Changing Nature of Warfare on Intelligence Collection and Processing for this year’s West Coast Security Conference. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points focused on the progression of technology and intelligence methods from the Second World War (WWII) to current conflicts shows ongoing improvement in data gathering and analysis, providing more accurate support for operations. Ever-expanding data volumes increase complexity, requiring more effective prioritization, validation, and simplification to maintain operational clarity. To prepare for the wars of the future, governments should focus on working closely with allies and preparing personnel for quick, informed action in dynamic operational conditions.